PENGUATAN BUDAYA LOKAL DALAM KERANGKA PENDIDIKAN KARAKTER: STUDI PADA BUDAYA JAWA - Adoniati Meyria Widaningtyas (Department of Anthropology, 2018)
Character education that planned since 2010 by the Ministry of National Education until seven years after the declaration still hasn’t shown significant impact for the Indonesian. The issue of globalization and the unstoppable flow of information perceive to begin erode the cultural values that become the identity of the Indonesian nation. Through Presidential Regulation Number 87/2017 on Strengthening Character Education, emphasized the principles of character education, one of which is local wisdom. One of Indonesia's local wisdom is the Javanese culture that characterizes the community in Central Java, East Java and Yogyakarta. This paper aims to explore the values of Javanese culture and relate it to the values of character education developed through strengthening the character education program, as well as giving ideas of its application in school.